Enhancing sustainability within industrial cooperative networks through the evaluation of economically compromised entities - Ismail, Muhammad; Al-Ansari, Tareq (Frontiers in Sustainability, 2023)
While promoting sustainable industrial cluster development using the circular economy perspective, the increased use of under-utilised materials results in compromised profitability in the cooperative network. The focus is to evaluate the external financial support required in industrial clusters against specific objectives and highlight the potential beneficiaries and losers in financial terms because of industrial symbiosis while closing material loops. This study provides an agent-based approach to record the system response based on three case studies to demonstrate the potential cost variations: The first case is about utilising naturally available resources only by all the industrial entities and is taken as a base case. Secondly, targeting the lowest cost for each product, and the third one provides a sustainable and flexible solution by targeting the best transformation methods and materials. The study concludes with valuable insights to identify the economically compromised entities in an industrial cluster network by considering economic deviations beyond a critical value. It can help take concrete measures in the form of incentives or investors subsidies by governmental organisations, regulators, and policymakers to intervene and stimulate markets through targeted financial support/policies to the compromised entities. This results in improved materials' loop closing, essentially promoting sustainable production systems in industrial clusters. Additionally, such financial support/incentives also influence the scarcity or accumulation of by-products or low-value materials, ultimately improving the industrial network's environmental and economic performance.